Quality of Health Services on Outpatient Satisfaction Levels: A Literature Review - Afni Basyariah Harahap; Ermi G; Sri Lestari Ramadhani Nasution (Journal of Community Health Provision, 2021)
The aims of the study is to determine the Service Quality on Outpatient Satisfaction Level. Patient satisfaction is a critical metric that is frequently used to assess the quality of health care services. Clinical outcomes, patient retention, and medical malpractice lawsuits are all affected by patient satisfaction. Patients are satisfied when they receive services that fulfill their expectations; they then opt to rate the services and behave based on their satisfaction. Service quality comprises five dimensions: reliability, responsiveness, assurance, empathy, and concrete value. Institutions must take numerous steps to ensure reliable services, including continual education and training of staff